Recent advancements in interface engineering of carbon fiber reinforced polymer composites and their durability studies at different service temperatures. Issue 7 (14th May 2022) - Gangineni, Pavan Kumar; Gupta K., B. N. V. S. Ganesh; Patnaik, Satyaroop; Prusty, Rajesh Kumar; Ray, Bankim Chandra
Abstract: A point of major concern in carbon fiber reinforced polymer (CFRP) composites is the interface between the carbon fibers (CFs) and the polymer matrix, which acts as the weakest link. Researchers have tried to work around this drawback by modifying the fiber or the matrix via the addition of nanofillers or using chemical treatment methods. In this review, the progress made in the last decade for enhancing the mechanical performance of CFRP composites by applying the aforementioned methods has been covered. Another aspect of CFRP composites that has limited their adaptability is their susceptibility both at sub‐zero and at elevated temperatures. In the later part of this review, the co‐relation between different service temperatures and the various mechanical properties of CFRP composites and has been elaborated upon. A better understanding of temperature dependent mechanical response would empower us to tailor the properties of CFRP composites depending on the in‐service temperature conditions. Abstract :